Implementation Of LEGO Play Therapy To Improve Fine Motor Skills In Preschool Children At PAUD Aulia, Bengkulu City, 2025 - Afriana, Venti; Susanti, Meri Epriana; Aprianti, Delta (Utami Publisher, 2026)
The prevalence of developmental disorders in Indonesia is still quite high at 27.5% (WHO, 2023), and about 13% of children aged 0–6 years experience developmental delays (Riskesdas, 2020). In Bengkulu City, especially in the Ratu Agung area, fine motor disorders are the most common cases, including at PAUD Aulia, where cases increased from 3 in 2023 to 5 in 2025.This study aims to provide nursing care and document the results of applying LEGO play therapy to improve fine motor skills in preschool children at PAUD Aulia, Bengkulu City, in 2025. The method used is a descriptive case study on one child (A.A) who had fine motor problems. The child showed difficulties in stacking blocks, drawing, holding a pencil, cutting, and buttoning clothes. The therapy was given for three days at PAUD Aulia.The results showed an improvement in fine motor skills; the child who previously could not complete three task indicators was able to perform them well after the therapy. This study concludes that LEGO play therapy is effective in improving fine motor skills in preschool children. The researcher recommends that this therapy be used more widely in early childhood education settings as a non-pharmacological intervention for health workers and educators.